Geochemical and Sr-Nd-Pb isotopic characteristics of extrusive rocks within the Çetmi Ophiolitic Mélange, Biga Peninsula - Güçtekin, Aykut (Ofioliti, 2018)
The different geochemical characteristics of the extrusive rocks of the Çetmi Ophiolitic Mélange (ÇOM) a remnant of the Intra-Pontide Suture (IPS) in the Biga Peninsula, NW Turkey, evidence the episodic formation of oceanic crust. Geochemically, volcanic rocks are divided into three groups: ocean island basalts (OIB), enriched mid-ocean ridge basalts (E-MORB) and basalts with supra-subduction zone (SSZ) affinity. While the OIB type samples were produced by small degrees partial melting from an enriched source, the E-MORB type samples point to mixing of enriched and depleted sources. In the OIB-type samples, the depletion of Zr and Hf compared to Nd as well as enrichment of Nb-Ta are attributed to presence of the amphibole in the mantle source. Radiogenic Pb isotope compositions towards EMII support metasomatic processes related to fractionation in the mantle reservoir. The SSZ samples are characterized by enriched light rare earth elements (LREE) and depleted high field strength elements (HFSE). The trace element characteristics of the SSZ samples indicate that a depleted MORB mantle source interacted with subduction-derived fluids due to the slab dehydration processes. Besides, the Sr-Nd-Pb isotope characteristics suggest that these samples originated from a MORB-type mantle source metasomatized by fluids or melts from subducted sediments. The major, trace element and isotopic data of the volcanic rocks in the ÇOM indicate that the oceanic lithosphere is generated along a SSZ-type spreading centre at an arc-basin system within the Intra-Pontide Ocean.